Entre sistema e ambiente: uma an??lise sist??mica da CGU e sua rela????o com os programas de compliance de empresas estatais brasileiras - Martins, Marina Soares Sabioni (2018)
The purpose of this dissertation was to interpret the processes of implementation of the integrity programs of state-owned enterprises regulated by the Federal Ministry of Transparency and General Comptroller's Office (CGU) from a systemic perspective, identifying interactions in internal control relational processes, verifying the existence of a anticorruption culture and analyzing the two poles, CGU and state-owned, as social systems. In order to reach the objectives, the methodology chosen was qualitative, where the first step is an exploratory study, where a case study was carried out in one of the four state-owned companies investigated by CGU in 2016, the "Alfa Company" and one second stage, where a single CGU case study was conducted, through semi-structured interviews with the coordinators of two areas: General Coordination of State Audit of Logistics and Services Sectors (CGLOG) and General Coordination of Institutional Development (CODIN) . For the analysis of the results obtained in the empirical research, the Social Systems Theory of Niklas Luhmann was chosen, besides bringing concepts of Complexity Theory for its better understanding. The results show that the CGU has some characteristics of the environment, when it irritates, disturbs and helps the stateowned when it provides rules and guidelines for the implementation of these programs, as a complex social system, when it closes operationally for the construction of its own mechanisms and structures of integrity. An attempt was made to build an organizational culture to combat corruption and create integrity mechanisms and procedures. The research has undergone changes of scenery in its course, making its analyzes even more complex.